Stress, Burnout dan Strategi Coping Perawat Frontline pada Waktu Pandemi COVID-19 - Nono, Risdayanto; Rosa, Else Maria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the stress, burnout, and coping of nurses during the COVID-19 pandemic in hospitals. The research method used is a literature review by selecting a theme and determining keywords (Keywords) and Boolean operators (AND, OR NOT, or AND NOT) before searching for scientific articles online. The literature search in this literature review used 4 databases, namely, Cochrane Library, Pubmed, Scopus, and ProQuest. The research results show that psychological symptoms that appeared in health workers due to the COVID-19 pandemic, such as depression, anxiety, stress, PTSD, fatigue, insomnia, and somatic symptoms, increased during the beginning of this pandemic. In conclusion, nurses experience a lot of work stress, medical professional burnout (emotional exhaustion, depersonalization, and a low sense of personal accomplishment), and mental health. Stress prevention should be adapted to the characteristics of the workplace, taking into account workplace optimization, social support, and compensation for workers' efforts. Keywords: Burnout, Coping Strategies, COVID-19, Nurses, Stress